Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1126/science.1191864
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of Culex quinquefasciatus Establishes a Platform for Mosquito Comparative Genomics

Abstract: Culex quinquefasciatus (the Southern house mosquito) is an important mosquito vector of viruses such as West Nile virus and St. Louis encephalitis virus as well of nematodes that cause lymphatic filariasis. It is one species within the Culex pipiens species complex and enjoys a distribution throughout tropical and temperate climates of the world. The ability of C. quinquefasciatus to take blood meals from birds, livestock and humans contributes to its ability to vector pathogens between species. We describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
456
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 438 publications
(472 citation statements)
references
References 10 publications
9
456
0
7
Order By: Relevance
“…Deep targeted sequencing for studying insecticide resistance Screening for genomic changes associated with insecticide resistance remained challenging until the sequencing of mosquito genomes (Holt et al 2002;Nene et al 2007;Arensburger et al 2010). Afterward, the development of mosquito DNA microarrays allowed screening for resistance genes based on their differential transcription, leading to the identification of detoxification genes conferring resistance (David et al 2005Strode et al 2008;Vontas et al 2010;Edi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Deep targeted sequencing for studying insecticide resistance Screening for genomic changes associated with insecticide resistance remained challenging until the sequencing of mosquito genomes (Holt et al 2002;Nene et al 2007;Arensburger et al 2010). Afterward, the development of mosquito DNA microarrays allowed screening for resistance genes based on their differential transcription, leading to the identification of detoxification genes conferring resistance (David et al 2005Strode et al 2008;Vontas et al 2010;Edi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We compared the An. gambiae genome with Culex quinquefasciatus, a distantly related species that is estimated to have last shared a common ancestor ∼145 million years ago (15,16), to find conserved chromosomal domains. Our approach differs from previous studies in vector competence, in which candidate genes were identified on the basis of changes in transcription profiles after parasite challenges.…”
mentioning
confidence: 99%
“…In culicines, such as Aedes and Culex, chromosomes are homomorphic and each pair, traditionally referred to as chromosomes 1, 2 and 3, undergoes recombination. In Culex and Aedes, chromosome 1 is sex determining; its p and q arms are largely syntenic to, respectively, the X chromosome and chromosomal arm 2R of Anopheles gambiae (Nene et al, 2007;Arensburger et al, 2010). In Aedes aegypti males, one chromosome of the chromosome 1 pair (hereafter called the M-chromosome, as opposed to the non-sex-specific m-chromosome) carries the SDR that does not recombine and harbors a dominant male-determining gene Nix (Hall et al, 2015).…”
Section: Introductionmentioning
confidence: 99%